PERANCANGAN SISTEM INFORMASI MANAJEMEN LAYANAN JASA TEKNOLOGI DAN KERJASAMA DI LEMBAGA DEF - Alfian Destha Joanda; Yusuf Priyandari; Roni Zakaria (Faculty of Computer Science Universitas Indonesia, 2014)
Layanan jasa seksi ABC information system is a system used by ABC lembaga DEF staff for process of saving and processing data of customer and customer’s product. This system facilitated by lembaga DEF to support making a document for testing. Previously seksi ABC lembaga DEF staff still use Microsoft Access and manual record. Therefore seksi ABC lembaga DEF staff require a new information system that quickly and efficiently so that improve customer services. In making this new information system the author uses Microsoft Visual Basic and MySql. The design of information system using prototyping method and using the database design with the concept of context diagram, Data flow Diagram (DFD), flowchart and Entity Relationship Diagram (ERD). The new application system is based on desktop applications and integration with SMS gateway.